Journal of Risk and Uncertainty - Viscusi, W. Kip.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Risk and Uncertainty welcomes original manuscripts, both theoretical and empirical, dealing with the analysis of risk-bearing behavior and decision making under uncertainty. The topics covered in the journal include, but are not limited to, decision theory and the economics of uncertainty, psychological models of choice under uncertainty, risk and public policy, experimental investigations of behavior under uncertainty, and empirical studies of real world risk-taking behavior. Manuscripts generally not considered for publication in the JRU include note-length submissions, papers dealing explicitly with finance, and papers in which risk and uncertainty are secondary concerns in the paper. An important aim of the JRU is to encourage interdisciplinary communication and interaction between researchers in the area of risk and uncertainty. Authors are expected to provide introductory discussions which set forth the nature of their research and the interpretation and implications of their findings in a manner accessible to knowledgeable researchers in other disciplines. Officially cited as: J Risk Uncertain.
Keywords: Operations research; Decision making; Economic theory; Microeconomics; Environmental economics; Economic Theory/Quantitative Economics/Mathematical Methods; Microeconomics; Operations Research/Decision Theory; Environmental Economics